Application of Project-Based Learning Model in Stage Management Course: Global Perspective - handayaningrum, warih; Pance Mariati (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
This article aims to explore the application of Project-Based Learning (PJBL) models in the course of stage management and to examine the global perspective regarding its implementation. In the context of the stage management course, PJBL can serve as an effective tool to involve students in practical and in-depth learning experiences. The implementation steps of the PJBL model are as follows: Firstly, the selection of challenging and relevant projects or tasks related to the field of stage management is carried out. Secondly, instructional planning is developed, including learning objectives, schedules, resources, and assessments. Subsequently, students are divided into working teams that will collaborate to complete the project. The learning process revolves around the project, with the instructor playing the role of a facilitator and guide. Through the implementation of the PJBL model, students are provided with opportunities to develop managerial skills, team collaboration, problem-solving, and more. Students also have the chance to learn from real experiences and apply management theories learned in practical situations. Furthermore, global competencies are also honed through this implementation, achieved by integrating elements of multiculturalism and cultural diversity within the given projects. In conclusion, the implementation of the PJBL model in the stage management course demonstrates significant potential in enhancing student engagement and facilitating deeper learning experiences. Taking a global perspective into account, this model can help students prepare themselves to face real-world challenges in the field of stage management.